2015
DOI: 10.1016/j.jmr.2014.12.020
|View full text |Cite
|
Sign up to set email alerts
|

REDOR solid-state NMR as a probe of the membrane locations of membrane-associated peptides and proteins

Abstract: Rotational-echo double-resonance (REDOR) solid-state NMR is applied to probe the membrane locations of specific residues of membrane proteins. Couplings are measured between protein 13CO nuclei and membrane lipid or cholesterol 2H and 31P nuclei. Specific 13CO labeling is used to enable unambiguous assignment and 2H labeling covers a small region of the lipid or cholesterol molecule. The 13CO-31P and 13CO-2H REDOR respectively probe proximity to the membrane headgroup region and proximity to specific insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 57 publications
(87 reference statements)
1
31
0
Order By: Relevance
“…To conduct this test, we used rotational echo double-resonance (REDOR) NMR spectroscopy, which measures the dipolar coupling between 13 C and 2 H nuclei. 13 C{ 2 H} REDOR is commonly used to probe protein-membrane interactions (31)(32)(33)(34). We found that leucine interacts with a hydrogen near the headgroup of decanoic acid but not at the end of the tail ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…To conduct this test, we used rotational echo double-resonance (REDOR) NMR spectroscopy, which measures the dipolar coupling between 13 C and 2 H nuclei. 13 C{ 2 H} REDOR is commonly used to probe protein-membrane interactions (31)(32)(33)(34). We found that leucine interacts with a hydrogen near the headgroup of decanoic acid but not at the end of the tail ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…45 FP insertion in a single leaflet is evidenced by NMR contacts between multiple FP residues and lipid tails. 59 There is not close contact between the FP and the MPER or between the FP and the TM, as evidenced by absence of NMR crosspeaks between these domains. 34…”
Section: Discussionmentioning
confidence: 99%
“…In summary, while the I=1/2 spin system suffers from lower sensitivity for this three-pulse ESEEM technique when compared to the I=1 for 2 H, 13 C has been able to be successfully used as the NMR-active nuclei in order to determine local secondary structure of a model membrane peptide for the first time. This technique using 13 C-labeled amino acids is comparable to REDOR solid-state NMR spectroscopy techniques; however, it requires less sample concentration (μM) and shorter data acquisition times (~30 minutes) making it ideal for studying membrane protein secondary structure [34,35]. This method provides an alternative approach to this biophysical technique in order to provide more versatility and options when used to study a variety of secondary structures.…”
Section: Discussionmentioning
confidence: 99%